Disentangling temporal changes in travel behavior: An age-period-cohort analysis based on German travel demand - Elisabeth Bartl; Alexander Bauer; Maximilian Weigert; Marion Karl; Jürgen Schmude; Helmut Küchenhoff (Annals of Tourism Research Empirical Insights)
Travel behavior changes over the temporal dimensions age, period, and cohort. However, longitudinal studies that simultaneously analyze and separate these temporal effects are missing. This study aims to disentangle the temporal changes in travel behavior (participation, frequency, expenses) and explain these changes through different theoretical lenses. Our analysis builds on large-scale representative secondary data from a repeated cross-sectional survey in Germany on the leisure travel behavior between 1983 and 2018 (N = 198,000) and uses generalized additive regression. Age and period are main drivers for changes in travel participation, cohort and age main drivers for changes in travel frequency over time. Relative travel expenses do not substantially change over time. Understanding temporal changes in travel behavior can support long-term planning in tourism.